2020
DOI: 10.1128/jb.00290-20
|View full text |Cite
|
Sign up to set email alerts
|

The Large pBS32/pLS32 Plasmid of Ancestral Bacillus subtilis

Abstract: The ancestral strain of Bacillus subtilis NCIB3610 (3610) encodes a large, low copy number plasmid called pBS32 that was lost during the domestication of laboratory strain derivatives. Selection against pBS32 may have been due to the fact that it encodes a potent inhibitor of natural genetic competence (ComI), as lab strains were selected for high frequency transformation. Previous studies have shown that pBS32 and its sibling pLS32 in Bacillus subtilis subsp. natto encodes a replication initiation protein (Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 133 publications
(199 reference statements)
1
8
0
1
Order By: Relevance
“…We then determined transformation frequencies and viability for these strains. As previously demonstrated, wild-type 3610 had an approximate transformation frequency of 10 -6 and curing the plasmid resulted in a 100-fold increase in transformation frequency (Figure 3B, black and dark blue) (10, 16). When comI was integrated on the chromosome in the cured strain, the transformation frequency was similar to the cured strain alone (Figure 3B, dark and light blue).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…We then determined transformation frequencies and viability for these strains. As previously demonstrated, wild-type 3610 had an approximate transformation frequency of 10 -6 and curing the plasmid resulted in a 100-fold increase in transformation frequency (Figure 3B, black and dark blue) (10, 16). When comI was integrated on the chromosome in the cured strain, the transformation frequency was similar to the cured strain alone (Figure 3B, dark and light blue).…”
Section: Resultssupporting
confidence: 72%
“…These systems rely on sensing elements created by the phage genome and respond by activating their killing module, in this case ComI. Secondly, nearly half the genes on pBS32 encode for a putative prophage, and it has been speculated that the entire plasmid could be a prophage phagemid (16). Thus, this model could represent a phage defense system in response to DNA uptake.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that microbial interactions, including horizontal genetic exchange, signaling, and metabolite exchange, occur between microorganisms in biofilm communities [1,[7][8][9]. It has been found that within a biofilm, bacteria of different taxa form a single genetic system in the form of plasmids and other MGE that carry a behavioral code for members of the biofilm and determine their trophic, energy, and other connections between themselves and the outside world [2,4,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental studies of this plan are few, especially when pathogenic enterobacteria and marine bacteria are co-cultivated. In this regard, studies seem to be very significant, allowing us to establish: to what extent the marine environment is a "cemetery" of microorganisms and to what time it is a "bridgehead" for the formation of epidemic variants of pathogenic bacteria [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Його результати представлені на таблицях та генетичних картах (таблиці 4.14, 4.15; рисунки 4.14, 4.16, 4.19).Характеристики секвенованих геномів добре укладаються в діапазон значень окремих ознак, властивих відповідним видам. Так, B. velezensis ONU 553 та B. subtilis ONU 559 позбавлені плазмід, що відомо для приблизно 80% штамів цих видів[27,54], а штам B. pumilus ONU 554 має плазміду, як це характерно для пpедставникiв виду[48].…”
unclassified